Thermo-hydro mechanical densification process of Nothofagus pumilio and Nothofagus antarctica and the effect of annual width ring on modulus of hardness, and dynamical mechanical properties - Jaka Gašper Pečnik; Matthew Schwarzkopf; Andreja Kutnar (Zenodo, 2018)
Conference abstract for Final COST Action FP1407 International Conference - Living with modified wood Pages 96-97